Acute pancreatitis in children – morbidity and outcomes at 1 year. Issue 1 (5th July 2022) - Bhanot, A; Majbar, AA; Candler, Toby; Hunt, LP; Cusick, E; Johnson, Paul R V; Shield, Julian PH
Abstract : Objective: To establish short-term and medium-term complications 1-year postdiagnosis, of acute pancreatitis (AP) in children aged 0–14 years. Design: One-year follow-up of a prospective monthly surveillance of new cases of AP in children under 15 years through the British Paediatric Surveillance Unit (BPSU) from April 2013 to April 2014. Setting: A monthly surveillance of >3700 consultant paediatricians and paediatric surgeons in the UK and Ireland using the BPSU. Patients: Children aged 0–14 years with a new diagnosis of AP. Main outcome measures: The outcomes following AP, including the incidence of complications and comorbidity at diagnosis and at 1 year. Results: Of the 94 new confirmed cases of AP identified in the UK during the study period, 90 cases (96%) were included in the 1-year follow-up. 30 patients (32%) developed further episode(s) of AP. Over one-fifth of patients developed one or more major complication. At initial admission, the most common of these was pancreatic necrosis (n=8, 9%), followed by respiratory failure (n=7, 7%). Reported complications by 1 year were pseudocyst formation (n=9, 10%), diabetes requiring insulin therapy (n=4, 4%) and maldigestion (n=1, 1%). At 1-year postdiagnosis, only 59% of children made a full recovery with no acute or chronic complications or recurrent episodes of AP. Two patients died, indicating a case fatality of ~2.0%. Conclusions: AP in childhood is associated with significant short-term and medium-term complications and comorbidities including risk of recurrence in approximately a third of cases.